Dynamic Modeling and Response of a Rotating Cantilever Beam with a Concentrated Mass - Yang Yong-feng; Wang Yan-lin; Chen Hu; Wu Min-juan (Shock and Vibration)
The rigid-flexible coupling system with a hub and concentrated mass is studied in this paper. Considering the second-order coupling of axial displacement which is caused by transverse deformation of the beam, the dynamic equations of the system are established using the second Lagrange equation and the assumed mode method. The simulation results show that the concentrated mass mainly suppresses the vibration and exhibits damping characteristics. When the nondimensional mass position parameter β>0.67, the first natural frequency is reduced as the concentrated mass increases. When β<0.67, the first natural frequency is increased as the concentrated mass increases. We also find the maximum first natural frequency nondimensional position for the concentrated mass.